Study of skeletal muscle formation in three-dimensional hydrogel - Muhammad Raihan Rozaili (Nanyang Technological University, 2021)
Engineered three-dimensional (3D) skeletal muscle tissues have wide applications in both tissue engineering and soft robotics. In our human body, skeletal muscles account for 30 – 45% of our body weight and play a crucial role in generating physical movement. However, they can be easily injured, and it is common for these muscles to not be able to fully restore after severe trauma, degenerative diseases, or other pathological conditions. Hydrogel-based 3D cellular models in the field of tissue engineering hold great promise for the generation of artificial muscles for muscle healing purposes. Additionally, in the field of soft robotics, engineered 3D skeletal muscles can function as an actuation scheme for biohybrid robots. In general, these cellular models are composed of myoblast cells embedded within a support material such as hydrogel. In this project, controlled experiments were conducted to investigate how skeletal muscle formation in 3D hydrogel is regulated by the mechanical properties, stress states, and geometric conditions of the hydrogel. The different mechanical properties and stress states were obtained by culturing and differentiating C2C12 myoblast cells into skeletal muscle tissue in collagen-based hydrogel scaffolds of varying concentrations and dimensions. Thereafter, the results were characterized by analysing optical microscopy images, in terms of properties such as cell morphology, after performing immunostaining on the samples. It was observed that the concentration of the hydrogel scaffold had the biggest impact on the formation of skeletal muscle, where a lower collagen concentration resulted in more defined and well-aligned mature myotubes. The size and shape of the substrate also influenced myotube formation, where the introduced tension forces facilitated the contraction and alignment of myotubes after myogenesis. Therefore, this project identifies mechanical cues that stimulate skeletal muscle formation in a 3D in vitro model for future application in regenerative medicine and soft robotics.